Treatment of Circadian Rhythm Sleep–Wake Disorders - Sun, Shi-Yu; Chen, Gui-Hai (Current Neuropharmacology, 2022)
Circadian rhythm sleep-wake disorders (CRSWDs) are a distinct class of sleep disorders caused by alterations to the circadian time-keeping system, its entrainment mechanisms, or a mismatch between the endogenous circadian rhythm and the external environment. The main clinical manifestations are insomnia and excessive daytime sleepiness that often lead to clinically meaningful distress or cause mental, physical, social, occupational, educational, or other functional impairment. CRSWDs are easily mistaken for insomnia or early waking up, resulting in inappropriate treatment. CRSWDs can be roughly divided into two categories, namely, intrinsic CRSWDs, in which sleep disturbances are caused by alterations to the endogenous circadian rhythm system due to chronic changes in the regulation or capture mechanism of the biological clock, and extrinsic circadian rhythm sleep-wake disorders, in which sleep disorders, such as jet lag or shift-work disorder, result from environmental changes that cause a mismatch between sleep-wakefulness times and internal circadian rhythms. Sleep diaries, actigraphy, and determination of day and night phase markers (dim light melatonin onset and core body temperature minimum) have all become routine diagnostic methods for CRSWDs. Common treatments for CRSWD currently include sleep health education, time therapy, light therapy, melatonin, and hypnotic drug therapy. Here, we review the progress in the epidemiology, etiology, diagnostic evaluation, diagnostic criteria, and treatment of intrinsic CRSWD, with emphasis on the latter, in the hope of bolstering the clinical diagnosis and treatment of CRSWDs.
Keywords: Circadian rhythm